The mechanism of improved thermal stability of protein-enriched O/W emulsions by soy protein particles. Issue 2 (22nd January 2020) - Ma, Wuchao; Wang, Jiamei; Wu, Di; Chen, Hui; Wu, Chao; Du, Ming
Abstract : Growing interest in nutritional and functional foods has motivated the design of protein-enriched products, which, however, is greatly challenged by undesirable aggregation and gelation of proteins induced by heating from pasteurization process. Abstract : Growing interest in nutritional and functional foods has motivated the design of protein-enriched products in the food industry, which, however, is greatly challenged by undesirable aggregation and gelation of proteins induced by heating from the pasteurization process. In this study, we reported the preparation of heat-stable soy protein particles (SPPs) by a simple preheating process (100 °C for 30 min) at pH 6.2 and 0.5% (w/v) protein concentration. As a proof of concept, the thermal stability of high-protein emulsions prepared by SPPs compared to native soy proteins (SPs) was investigated. The results showed that high-protein emulsions stabilized by SPPs exhibited appreciable heat stability, whereas SPs gelled when both samples were tested at an identical concentration (10%, w/v). In addition, the emulsions prepared by SPPs demonstrated lower values of storage modulus and viscosity along with a stable size by heat treatment as well as a more stable coated protein layer, in contrast to those prepared by SPs presenting macroscopic aggregation and an unstable coated protein layer. The results would provide valuable information in terms of the development of heat-stable, high-protein, and well-dispersed food emulsions that may find numerous applications in the food industry.